The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/codi.16243
|View full text |Cite
|
Sign up to set email alerts
|

Impact of operation duration on postoperative outcomes of minimally‐invasive right colectomy

Abstract: Aim: Operation time (OT) is a key operational factor influencing surgical outcomes. The present study aimed to analyse whether OT impacts on short-term outcomes of minimally-invasive right colectomies by assessing the role of surgical approach (robotic [RRC] or laparoscopic right colectomy [LRC]), and type of ileocolic anastomosis (i.e., intracorporal [IA] or extra-corporal anastomosis [EA]). Methods: This was a retrospective analysis of the Minimally-invasivE surgery for oncological Right ColectomY (MERCY) St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…A meta-analysis was used to evaluate the e cacy of overlapping triangulation and other anastomosis procedures. No statistically signi cant differences were found between overlapping triangular anastomosis and other anastomoses in terms of operative time, intraoperative bleeding and number of lymph nodes dissected after analysis by randomized controlled study through a multicenter study [32] ,it is suggested that different anastomosis methods have little in uence on these outcome indexes. In this study, we pooled 7 studies and found that there was no signi cant difference in operation time between overlapping triangular anastomosis and other anastomosis procedures.…”
Section: Discussmentioning
confidence: 86%
“…A meta-analysis was used to evaluate the e cacy of overlapping triangulation and other anastomosis procedures. No statistically signi cant differences were found between overlapping triangular anastomosis and other anastomoses in terms of operative time, intraoperative bleeding and number of lymph nodes dissected after analysis by randomized controlled study through a multicenter study [32] ,it is suggested that different anastomosis methods have little in uence on these outcome indexes. In this study, we pooled 7 studies and found that there was no signi cant difference in operation time between overlapping triangular anastomosis and other anastomosis procedures.…”
Section: Discussmentioning
confidence: 86%
“…Against this background, the present trial was designed to compare the clinical benefits and risks of discontinuing antiplatelet drugs with LMWH bridging therapy. Fourth, numerous other factors, such as functional status, comorbidity, mental health status [ 62 ], and duration of surgery [ 63 ], may have confounded the relationship between age and clinical outcomes [ 64 ]. Additionally, frailty may affect a patient’s ability to tolerate, survive, and eventually recover from surgical stress [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of the MERCY Study Group database indicated that operative time of ≥200 minutes was significantly associated with complications. 29 Shen et al reported that operation duration was an independent risk factor for patient's short-term and long-term outcomes after radical colorectal surgery. Thus, prolonged operative time was a risk operational factor influencing postoperative complications, which reflected more complex surgical procedures.…”
Section: Discussionmentioning
confidence: 99%